2020
DOI: 10.1038/s41419-020-03169-3
|View full text |Cite
|
Sign up to set email alerts
|

Exosomal circ_DLGAP4 promotes diabetic kidney disease progression by sponging miR-143 and targeting ERBB3/NF-κB/MMP-2 axis

Abstract: Diabetic kidney disease (DKD) is closely associated with the high risk of cardiovascular disease and mortality. Exosomal circRNAs can exert significant roles in the pathology of various diseases. Nevertheless, the role of exosomal circRNAs in DKD progression remains barely known. Circular RNA DLGAP4 has been reported to be in involved in acute ischemic stroke. In our study, we found exosomal circ_DLGAP4 was increased in the exosomes isolated from HG-treated mesangial cells (MCs), DKD patients, and DKD rat mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
51
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…Exosomes were first considered to be "garbage bags" that remove waste proteins and metabolites. However, recent studies have shown that the exosomal cargo is biologically active (8) and mediates intercellular communication (9). Several exosomes-enriched proteins, including cytoskeletal proteins, fusion-related proteins, tetrapeptides (CD9, CD63, CD81 and CD82) and membrane connectins (10,11), as well as oncoproteins (12), have been reported on in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Exosomes were first considered to be "garbage bags" that remove waste proteins and metabolites. However, recent studies have shown that the exosomal cargo is biologically active (8) and mediates intercellular communication (9). Several exosomes-enriched proteins, including cytoskeletal proteins, fusion-related proteins, tetrapeptides (CD9, CD63, CD81 and CD82) and membrane connectins (10,11), as well as oncoproteins (12), have been reported on in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to normal glucose (NG)-treated GEC exosomes, 217 circRNAs were significantly down-regulated while 484 were up-regulated in HG-treated GEC exosomes ( 70 ). The level of circ_DLGAP4 was also shown to be increased in exosomes isolated from HG-treated MCs ( 71 ). Moreover, its expression was consistently elevated in DKD rat models, DKD patients, and further increased in DKD patients with macroalbuminuria, suggesting it might correlate with DKD progression.…”
Section: Circrnas As Novel Biomarkers For Kidney Diseasesmentioning
confidence: 99%
“…Interestingly, results of several studies in DKD indicated that different circRNAs could act as the same miRNA's sponge. For example, miR-143 was confirmed to be targeted by both circ_DLGAP4 and circ_0000064 in MCs, whose increased expression consistently promoted cell proliferation and fibrosis ( 71 , 101 ). As mentioned above, circ_WBSCR17 functioned through sponging miR-185-5p in TECs.…”
Section: Circrnas As Therapeutic Targets For Kidney Diseasesmentioning
confidence: 99%
“…Gpnmb Naglu NF-κB activation Inflammation circ_0114427 (Cao et al, 2020) miR-494 AFT3 NF-κB activation circ-AKT3 (Xu et al, 2020) miR-144-5p Wnt/β-catenin pathway Wnt/β-catenin activation circ-YAP1 (Huang et al, 2020) miR-21-5p PI3K/AKT/mTOR pathway PI3K/AKT/mTOR activation circ-VMA21 (Shi et al, 2020) miR-9-3p SMG1 Oxidative stress Chronic kidney disease circHLA-C (Luan et al, 2018) miR-150 Undefined Fibrosis-associated genes express circRNA_15698 (Hu et al, 2019) miR-185 TGF-β1 Extracellular matrix-related protein synthesis circ_WBSCR17 (Li et al, 2020a) miR-185-5p SOX6 ECM accumulation circRNA_002453 (Ouyang et al, 2018) Undefined Undefined Biomarker in blood circ_DLGAP4 (Bai et al, 2020) miR-145 ERBB3/NF-κB/MMP-2 pathway Inflammation circLRP6 miR-205 HMGB 1/TLR4/NF-κB pathway Inflammation circRNA_010383 (Peng et al, 2020) miR-135a TRPC1 ECM accumulation circ-AKT3 (Tang et al, 2020) miR-296-3p E-cadherin ECM accumulation circNr1h4 (Lu et al, 2020) miR-155-5p Far1 Reactive oxygen cANRIL (Deng et al, 2019) miR-9 NF-κB and JNK/p38 pathways Inflammation Renal cell carcinom has_circ_001895 miR-296-5p SOX12 Promoting proliferation, migration, invasion, inhibiting apotosis circEGLN3 (Lin and Cai, 2020) miR-1299 IRF7 Promoting proliferation, migration, invasion, inhibiting apotosis circNRIP1 (Dong et al, 2020) miR-505 AMPK and PI3KL/AKT/mTOR pathways Promoting proliferation, migration, invasion, inhibiting apotosis circNUP98 (Yu et al, 2020) miR-567 PRDX3 Promoting proliferation, migration, invasion, inhibiting apotosis has_circ_0072309 miR-100 PI3KL/AKT/mTOR Inhibiting proliferation, migration, invasion, promoting apotosis circC3P1 miR-21/PTEN PI3K/AKT and NF-κB Inhibiting proliferation, migration, invasion, promoting apotosis circFNDC3B miR-99a JAK1/STAT3 and MEK/ERK pathways Promoting proliferation, migration circ-ZNF652 (Zhang and Guo, 2020) miR-205 JAK1/STAT3 and MEK/ERK pathways Promoting proliferation, migration circ-ZNF609 (Xiong et al, 2019) miR-138-5p FOXP4 Promoting proliferation, invasion circDHX33 (Wang et al, 2020) miR-498-3p MERK Promoting proliferation, invasion circHIPK3 miR-508-3p CXCL13 Promoting proliferation, migration, invasion circUBAP2 (Sun et al, 2020) miR-148a-3p FOXK2 Promoting proliferation, migration, invasion circ_001842 (Zeng et al, 2020) miR-502-5p SLC39A14 Promoting proliferation, migration, invasion cRAPGEF5 miR-27a-3p TXNIP Inhibiting proliferation, migration has_circ_0001451 associated genes (Zhou et al, 2013;…”
Section: Circular Rnas In Chronic Kidney Diseasesmentioning
confidence: 99%
“…What’s more, it has been reported that silencing cANRIL (circular antisense noncoding RNA in the INK4 locus) alleviates inflammatory responses and blocks NF-κB and JNK/p38 pathways by positively regulating miR-9 in LPS-induced CKD modle ( Deng et al, 2019 ). While The increased circ_DLGAP4 sponges with miR-143 and activates ERBB3/NF-κB/MMP-2 to promote fibrosis of mesangial cells ( Bai et al, 2020 ). circLRP6 was found to be upregulated in high glucose (HG)-treated mesangial cells, regulated HG-induced cell injure via sponging miR-205, upregulating HMGB1 and activating TLR4/NF-κB pathway (Chen et al, 2019).…”
Section: Circular Rnas In Chronic Kidney Diseasesmentioning
confidence: 99%